ENGINEERING CAMPUS IS EXPECTED TO CONTINUE TRADITION OF EXCELLENCE - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
NIBONG TEBAL, August 2015 – The Engineering Campus (KK) of Universiti Sains Malaysia (USM) is expected to continue to cultivate a culture of excellence among its faculty, students and staff and make the University proud.